The Epidemiology of HIV Among Young People in Sub-Saharan Africa: Know Your Local Epidemic and Its Implications for Prevention. - Napierala Mavedzenge, Sue; Olson, Rick; Doyle, Aoife M.; Changalucha, John; Ross, David A. (Journal of Adolescent Health, 2011)
Abstract: Background: Broad patterns of HIV epidemiology are frequently used to design generic HIV programs in sub-Saharan Africa. Methods: We reviewed the epidemiology of HIV among young people in sub-Saharan Africa, and explored the unique dynamics of infection in its different regions. Results: In 2009, HIV prevalence among youth in sub-Saharan Africa was an estimated 1.4% in males and 3.4% in females, but these values mask wide variation at regional and national levels. Within countries there are further major differences in HIV prevalence, such as by sex, urban/rural location, economic status, education, or ethnic group. Within this highly nuanced context, HIV prevention programs targeting youth must consider both where new infections are occurring and where they are coming from. Conclusions: Given the epidemiology, one-size-fits-all HIV prevention programs are usually inappropriate at regional and national levels. Consideration of local context and risk associated with life transitions, such as leaving school or getting married, is imperative to successful programming for young people.